Annual eradication rate of bismuth‐containing quadruple therapy as second‐line treatment for Helicobacter pylori infection: A 15‐year prospective study at a tertiary hospital in Korea. Issue 3 (6th March 2020) - Yoon, Kichul; Kim, Nayoung; Lee, Jung Won; Yoon, Hyuk; Shin, Cheol Min; Park, Young Soo; Lee, Dong Ho
Abstract: Background: Bismuth‐containing quadruple therapy is widely used as second‐line treatment for Helicobacter pylori infection. This prospective study investigated the changes in the annual H. pylori eradication rates of quadruple therapy. Methods: This study included an intention‐to‐treat (ITT) population of 452 subjects who failed first‐line eradication therapy for H. pylori between 2003 and 2018. All subjects received a 14‐day course of bismuth‐containing quadruple therapy consisting of esomeprazole (40 mg twice daily), metronidazole (500 mg thrice daily), bismuth subcitrate (120 mg four times daily), and tetracycline (500 mg four times daily). Per‐protocol (PP) analysis of data was performed in subjects who followed up with strict treatment adherence. Eradication was confirmed based on the results of the 13 C‐urea breath test, rapid urease test (CLOtest ® ), and histopathologic evaluation. Compliance and adverse effects were also investigated. A minimal inhibitory concentration test was performed on tissue samples obtained from 103 subjects. Results: The overall eradication rates following ITT and PP analyses were 78.8% (356/452) and 89.5% (314/351), respectively. The annual eradication success rate did not show significant changes ( P = .062 [ITT], P = .857 [PP]) over the 15‐year study period. Adverse events were reported in 57.3% of the ITT population. The rates of resistance to metronidazole and tetracycline were 44.7% and 18.4%, respectively. Conclusions: Despite high antibiotic resistance rates, no significant reduction in annual eradication rates was observed during the study period.